Ultrasonographic features of epididymitis in dogs: a case series - Spada, Stefano; Russo, Marco; Arlt, Sebastian P.; Frehner, Bianca L.; Pagani, Gaia; Carvalho, Joana Rodrigues; Jainek, Hélène; Ambrosio, Nicola; De Felice, Daniela; Herbel, Johannes (Frontiers in Veterinary Science, 2025)
IntroductionEpididymitis in dogs is an underreported but clinically relevant condition, often associated with scrotal pain, systemic inflammation, and infertility. Diagnosis commonly relies on clinical and ultrasonographic findings, even though information concerning the latter are poorly documented. This report aims to describe the ultrasonographic features of epididymitis in a series of clinical canine cases, including clinical and laboratory findings.Materials and methodsClinical cases of dogs affected by epididymitis were retrospectively included. Clinical signs, andrological findings, ultrasonographic abnormalities of the epididymis and testicles, blood analysis and, where available, cytological or histopathological data were recorded. Ultrasonographic features evaluated included epididymal size, capsular integrity, echotexture, vascularization, presence of mineralization and scrotal effusion.ResultsFourteen dogs with epididymitis were included, and the condition was unilateral in 11 dogs (eight left-sided) and bilateral in three. On B-mode ultrasound the epididymal tail was the most frequently affected portion. Other frequent findings included epididymal enlargement, capsular irregularity, and inhomogeneous echotexture. Mineralization, hypoechoic cavities, and peri-epididymal oedema were observed, but not present in all cases. Concurrent testicular and urogenital abnormalities, along with leucocytosis and neutrophilic left shift, were common in acute cases.ConclusionThis is the first case series describing ultrasonographic patterns of epididymitis in dogs. Early recognition via ultrasound may support targeted treatment and fertility preservation.